STRUCTURE INVESTIGATION OF THE CULTURAL HERITAGE BUILDING JOHAR MARKET AT SEMARANG - Sriwati Purnomo; Juniantoro Suryanto; Ivan Sandi Darma; Antonius Ardiyanto (AGORA:Jurnal Penelitian dan Karya Ilmiah Arsitektur Usakti, 2021)
Johar Market in Semarang is a cultural heritage building made of concrete. Burned May 9, 2015. The fire damaged non-structural elements of structural elements.The purpose of this investigation is to complete the unavailability of structural data as a discussion material to determine the rehabilitation process.This research uses descriptive qualitative method. Describes in detail the initial structure investigation process in 2017.This structural investigation is a combination of destructive and non-destructive tests, to determine the condition and extent of damage to the Johar Market building. The results of this entire investigation will determine the sustainability of the conservation of the Johar market.